Global population surpasses eight billion: Are we ready for the next billion? - Nityanand Jain; Islam Kourampi; Tungki Pratama Umar; Zahra Rose Almansoor; Ayush Anand; Mohammad Ebad Ur Rehman; Shivani Jain; Aigars Reinis (AIMS Public Health, 2023)
In November 2022, the global population had officially crossed eight billion. It has long been recognized that socioeconomic or health-related problems in the community always accompany an uncontrolled population expansion. International calls have been made regarding lack of universal health coverage, an insufficient supply of healthcare providers, the burden of noncommunicable disease, population aging and the difficulty in obtaining safe drinking water and food. The present health policy paper discusses how to conquer these crowded world issues, including (1) promoting government and international organization participation in providing appropriate infrastructure, funding and distribution to assist people's health and well-being; (2) shifting health program towards a more preventive approach and (3) reducing inequalities, particularly for the marginalized, isolated and underrepresented population. These fundamental principles of health policy delivery as a response to an increasingly crowded world and its challenges are crucial for reducing the burden associated with excessive healthcare costs, decreased productivity and deteriorating environmental quality.